MIS-C, inherited metabolic diseases and methylmalonic acidemia: a case report and review of the literature - Maria Cristina Maggio; Cinzia Castana; Marina Caserta; Antonella Di Fiore; Vittoria Siciliano; Giovanni Corsello (Italian Journal of Pediatrics)
Abstract Background Methylmalonic acidemia (MMA) secondary to mutase deficiency, mut0, is an inborn error of metabolism causing complete enzyme defect, allowing a high risk of irreversible complications, secondary to metabolic decompensation, induced by infections and the hyperinflammatory state. Multisystem Inflammatory Syndrome in Children (MIS-C) is a hyperinflammatory syndrome that manifests 14–60 days after the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection in patients aged < 21 years. Only a few cases of patients with inherited metabolic diseases (IMD) and MIS-C are described. However, to our knowledge, this is the first case of MMA with MIS-C. Case presentation We describe a 2-year-old child with MMA secondary to mutase deficiency, carrying the homozygous mutation c.2179 C > T of MMUT gene, associated to mut0 phenotype. One month after SARS-CoV-2 infection, he presented fever, rash, significant increase of C-reactive protein (CRP), ferritin, triglycerides, interleukin (IL)-6, N-terminal fragment of the pro brain natriuretic peptide (NT-pro-BNP), compatible with the diagnosis of MIS-C. He was treated with intravenous immunoglobulins and methylprednisolone, with rapid clinical improvement. Ten days later, he showed the worsening of clinical and hematological parameters, associated with anemia, thrombocytopenia, metabolic acidosis, hyperlactatemia, increased urinary methylmalonic acid, leading to multiorgan failure (MOF). He was treated with high caloric intake nutrition by intravenous carbohydrates infusion; sodium bicarbonate, thiamine, carnitine, coenzyme Q, vitamin C, antibiotics, methylprednisolone and anakinra. Three days after the start of anakinra, a significant improvement in clinical and biochemical parameters occurred. Twenty days later, a sepsis from Methicillin-resistant Staphylococcus Aureus and Candida Albicans required the interruption of anakinra, with the decline of the clinical conditions and the exitus. Conclusions In patients with a severe form of MMA and MIS-C anakinra is a safe treatment. MOF and metabolic decompensation, secondary to the hyperinflammatory state typical of MIS-C, can be successfully treated with targeted therapy against proinflammatory cytokines. The description of these clinical cases is a precious lesson in managing IMD therapeutic emergencies. Paediatricians must provide a strict monitoring of metabolic compensation, to avoid irreversible complications.